Influence of tidal stress on the immunocompetence of hemocytes in soft-shell clam (Mya arenaria) - A. Beaudry; C. Brousseau-Fournier; G. Alix; M. Fortier; M. Auffret; P. Brousseau; M. Fournier (MDPI AG, 2013)
Not available